A abordagem de problemas sociais em um livro didático de inglês: efeitos de sentido a partir da análise materialista de discurso - Silva, Guilherme Benedito Pereira da (2023)
The proposed theme of the work aims to discuss the patrimonial responsibility of political parties in order to analyze the application, scope, relativization or flexibility of the non-seizability described in art. 833, item XI, of the Code of Civil Procedure (nonseizability of the party fund), especially after the creation of the electoral fund, which transformed mixed campaign financing in Brazil into predominantly public funding. The research seeks to answer the following questions: which values of the Parties can be the object of expropriation by creditors and interested parties who aim to receive debts? If the Parties do not have private funds, is it possible to make the party fund nonseizability more flexible? In which contexts? Should the special fund also be declared unseizable like the party fund? Through the deductive method of investigation, we seek to understand the peculiarities of the patrimonial responsibility of political parties. As a delimitation of the proposed theme, the main core of the research is the objective dimension of patrimonial responsibility, that is, it is limited to the analysis of which values can be expropriated. Therefore, the theme is approached in an evolutionary way and the dissertation was divided into three chapters. The first, in an introductory way, aims to address general concepts of electoral law, such as political parties, candidates, federations, coalitions, together with political financing in Brazil. The second chapter aims to study the general part of patrimonial responsibility and the regime of non-seizability. The third chapter deals specifically with the current context of party debts and the executions in which the parties are submitted, both in the scope of the Common Justice and in the scope of the Specialized Electoral Justice, specifically analyzing the non-seizability of party funds and electoral fund, in order to facilitate the receipt of amounts from political parties by creditors. Therefore, the area of concentration Process, Techniques and Protection of Existential and Patrimonial Rights of the Graduate Program in Procedural Law of the Federal University of Espírito Santo.